Mapping IranDoc Brand Associations Network from the Stakeholders’ Viewpoint - Somayeh Labafi (Iranian Journal of Information Processing & Management, 2021)
The dominance of pragmatic paradigm in science and technology policy has changed the approach to the management of scientific institutes. In pragmatic paradigm, scientific institutes should be able to respond stakeholders’ needs and requirements. This study aims to mapping brand associations network of IranDoc from the stakeholders' viewpoint. In order to mapping IranDoc brand associations network, brand concept map method was used. Brand concept map as a qualitative method has three stages of elicitation, mapping and aggregation. The statistical population of the research is the stakeholders of IranDoc Research Institute. The sampling method in elicitation and mapping stages are purposeful and sample size in both stages includes seventy people. IranDoc brand associations network has eighteen core associations. The core positive associations include prevention of plagiarism, search for scientific document, scientific sources, thesis, access to information, Ganj, electronic resources, scientific communication, research ethics, scientific accuracy, systems, science promotion, universities, information management, science policy, and the core negative associations include bureaucracy, multiple systems, and poorly designed sites. IranDoc brand associations network has two layers of associations. The analysis of IranDoc brand associations network shows low mental involvement of stakeholders with IranDoc brand and dispersion of stakeholder mentality about IranDoc brand. Thesis and plagiarism prevention have the strongest connection with IranDoc brand.